A Research on the Impact of Creditor’s Indigence on the Issue of Debt Exemptions - Musa Hakimi Sadr; Fatemeh Raja'ei (آموزه‌‌های فقه مدني, 2020)
One of the issues in civil courts has been the exemptions of debt from the past to the present. Jurists and jurisconsult in this issue believe that if debtor owes no property except his home and some other necessities of life, creditor cannot force him to sell the property. Different aspects of debt exemptions have been explored in jurisprudence books and jurisprudential and juridical researches, but what has not been addressed is the impact of financial conditions of the creditor on debt exemptions arbiter. The question of whether the creditor is still in penury can also order the debtor with the exception of some property of debtor? This is the question that has been tried to be answered in this research through jurisprudential, traditionary and law books. In the end, after examining the reasons for the debt exemptions, which are mainly narrations and the rule of distress and constriction negation, what is stated as an answer to this question is that these reasons does not apply to the case where creditor himself or herself is in distress and constriction (insolvency), therefore, debtors’ property can be withdrawn as long as distress and constriction (insolvency) be removed from creditor, even if it is his (debtor) house. if creditor is in distress and constriction (insolvency).